2021
DOI: 10.2147/idr.s299106
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasma gondii Among Pregnant Women Attending Antenatal Care in Northwest Ethiopia

Abstract: Introduction Toxoplasmosis is a life-threatening disease in pregnant women, having social and economic impacts due to congenital toxoplasmosis. However, in Ethiopia, it is neglected zoonotic disease, which requires screening and identifying risk factors in pregnant women to plan a public health intervention. Methods This institutional-based cross-sectional study was employed from March to April 2019 to estimate the seropositivity and assess potential risk factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
2
7
2
Order By: Relevance
“…There was no significant difference in prevalence of T. gondii of participant based on age of mothers. This result was in accordance with other findings ( 2 , 33 , 34 ). In the studies of Bienkowski et al ( 1 ) and Nowakowska et al ( 4 ) the relationship between age and serological test results was direct and significant, that are in opposition with our results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There was no significant difference in prevalence of T. gondii of participant based on age of mothers. This result was in accordance with other findings ( 2 , 33 , 34 ). In the studies of Bienkowski et al ( 1 ) and Nowakowska et al ( 4 ) the relationship between age and serological test results was direct and significant, that are in opposition with our results.…”
Section: Discussionsupporting
confidence: 94%
“…This could be due to the cold weather of the region. This infection is more common in hot humid areas ( 2 , 33 ). Another probable reason is that the study was conducted in the urban area.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to studies in Ethiopia where contact with soil was found as a risk factor [33,34]. The association of trading as a risk factor for testing seropositive was also reported in Ethiopia [35]. Farming remains an important risk factor as oocysts in the soil persist with infective potential for about 12-24 months [36] or farmers are likely to be exposed to undercooked meat, salad and fruits [37].…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with this, lineages shared with other global geographical areas are present in Africa and unique African haplogroups ( 111 113 ). Studies of seroprevalence indicate that carriage of T. gondii is common in the African population ( 114 , 115 ), with recent reports indicating that seroprevalences vary broadly depending on region and age and range on average between 30-70% ( 116 121 ). The seroprevalence levels in humans go together with the reported prevalence in animals used for meat consumption ( 113 , 122 ).…”
Section: Cerebral Toxoplasmosis In Africamentioning
confidence: 98%
“…Blood serologic tests are broadly used in Africa for general diagnostics (116)(117)(118)(119)(120). Further, detection of T. gondii DNA by PCR in the cerebrospinal fluid is of high diagnostic value for CNS manifestations (173).…”
Section: Value Of Neuroimmune Changes In Diagnostics and Therapiesmentioning
confidence: 99%